RELATIONSHIP OF ACL INJURY WITH POSTERIOR TIBIAL SLOPE, INTERCONDYLAR NOTCH WIDTH RATIO, AGE, AND SEX - Boby Harul Priono; Ghuna Arioharjo Utoyo; Yoyos Dias Ismiarto (Journal Orthopaedi and Traumatology Surabaya, 2018)
Posterior tibial slope (PTS) has been proposed as a potential risk factor for ACL injury; however, studies that examined this relationship have provided inconclusive and sometimes contradictory results. Further characterization of this relationship may enable the medical community to identify individuals at greater risk for ACL injury and possibly characterize an anatomic target during surgical reconstruction. Medical records of 20 patients who underwent MRI of the knee and athroscopy procedure between August 2016 and March 2017 were reviewed. Patients were separated into 2 groups: a study group of those subjects who had undergone surgery for ACL injury (n =10) and a control group of patients diagnosed without ACL Injury (n = 10). Demographic data were collected, and MRI images from both groups were analyzed using protactor android imaging software to obtain PTS measurements. Data then analyzed using SPSS v20. Data analysis demonstrated that the ACL injury group had significantly greater values for PTS (14.4 SD ± 3.5) compared with controls (10.1 SD ± 2.6). After stepwise elimination of non significant variables, the final t test independent determined that PTS (p value 0.08; p < 0.1) had statistically significant relationships with ACL injury. INW ratio, age, and sex were not demonstrated to be significant predictors of ACL injury in this final model. This study showed a relationship between increased PTS and ACL injury, which corroborates the findings of previously published studies. INW ratio, sex, and age showed no significant relationship with ACL injury.